2004
DOI: 10.1242/jeb.01069
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and serotonergic innervation of cockroach salivary glands:distribution and morphology of synapses and release sites

Abstract: SUMMARY The paired salivary glands in the cockroach are composed of acini with ion-transporting peripheral P-cells and protein-secreting central C-cells, and a duct system for the modification of the primary saliva. Secretory activity is controlled by serotonergic and dopaminergic neurons, whose axons form a dense plexus on the glands. The spatial relationship of release sites for serotonin and dopamine to the various cell types was determined by anti-synapsin immunofluorescence confocal microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Previous immunofluorescence studies have demonstrated that the ducts further downstream of the acini are innervated only by dopaminergic fibres that have some release sites (Baumann et al, 2002;Baumann et al, 2004). Thus, we expected that duct cells would respond to stimulation by DA, but not by 5-HT.…”
Section: -Ht-induced Changes In Ph I and [Ca 2+ ] I In Duct Cells Rementioning
confidence: 87%
See 1 more Smart Citation
“…Previous immunofluorescence studies have demonstrated that the ducts further downstream of the acini are innervated only by dopaminergic fibres that have some release sites (Baumann et al, 2002;Baumann et al, 2004). Thus, we expected that duct cells would respond to stimulation by DA, but not by 5-HT.…”
Section: -Ht-induced Changes In Ph I and [Ca 2+ ] I In Duct Cells Rementioning
confidence: 87%
“…Salivation is controlled by dopaminergic and serotonergic neurons (Baumann et al, 2002;Baumann et al, 2004). Acinar peripheral cells are specialised for electrolyte and water transport and are innervated by dopaminergic and serotonergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These biogenic amines were believed is vital in physiological events of salivary glands [5]. In cockroach, salivation is regulated by the salivary duct nerve that consists of two neurons: dopaminergic and serotonergenic [6][7][8]. Both of these compounds were found to stimulate the salivation in isolated SG [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SN1 and SN2 axons with a thickness of several micrometers, the SDN contains thinner axons that also project from the SOG towards the salivary gland. These thin axons contain serotonin (5-hydroxytryptamine; 5-HT) as neurotransmitter (Davis, 1985;Baumann et al, 2002;Baumann et al, 2004). An additional source of serotonergic innervation of the salivary gland is provided by the stomatogastric nervous system (Whitehead, 1971;Bowser-Riley et al, 1978;Baumann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The P-cells are innervated by both dopaminergic and serotonergic fibers, and are responsible for ion and water transport. The C-cells are innervated solely by serotonergic fibers and are responsible for protein secretion (Baumann et al, 2002;Baumann et al, 2004). Thus, with dopamine stimulation, a protein-free saliva is produced in the acini whereas 5-HT stimulates the secretion of protein-containing saliva (Just and Walz, 1996;Marg et al, 2004;Rietdorf et al, 2005;Troppmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%